2017
DOI: 10.3892/mmr.2017.6479
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression in esophageal squamous cell carcinoma: Novel diagnostic and prognostic biomarkers

Abstract: Abstract. The aim of the present study was to identify more effective molecular diagnostic biomarkers for esophageal squamous cell carcinoma (ESCC). The non-coding RNA profile GSE43732, generated from 238 paired frozen tissues from 119 patients, was analyzed. Raw data were preprocessed and the differentially expressed miRNAs were screened by limma package with log 2 fold change >2. Prognosis-associated miRNAs were identified using receiver operating characteristic (ROC) and Kaplan-Meier (KM) curve analysis. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Notably, serum samples from patients who experienced progression exhibited higher levels of exosomal miR-143-3p during radiotherapy than those at baseline, suggesting its potential utility in the development of liquid biopsy techniques. A study also reported a notable increase of hsa-miR-143-3p in ESCC tissues compared with that in adjacent normal tissue, along with its association with prognosis [ 48 ], which supported our results. Moreover, given the multitude of genomic alterations and the restricted effectiveness of therapies targeting cancer cells, recent research efforts have concentrated on acquiring a broader comprehension of the TME and potential strategies to alter it to facilitate cancer treatment [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, serum samples from patients who experienced progression exhibited higher levels of exosomal miR-143-3p during radiotherapy than those at baseline, suggesting its potential utility in the development of liquid biopsy techniques. A study also reported a notable increase of hsa-miR-143-3p in ESCC tissues compared with that in adjacent normal tissue, along with its association with prognosis [ 48 ], which supported our results. Moreover, given the multitude of genomic alterations and the restricted effectiveness of therapies targeting cancer cells, recent research efforts have concentrated on acquiring a broader comprehension of the TME and potential strategies to alter it to facilitate cancer treatment [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, hUCMSCsexo represses the progression of pancreatic ductal adenocarcinoma by delivery of exogenously loaded miR-145-5p [10]. Numerous microRNAs (miRNAs or miRs), including miR-375, have been highlighted as promising diagnostic and prognostic biomarkers for ESCC patients [11][12][13]. Downregulation of miR-375 is a frequent observation in ESCC, which correlates with poor prognosis, low survival rate, and tumor metastasis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…According to dbDEMC and miR2Disease's evidence, 44 of the top 50 predicted miRNAs were verified (see Table 8). For example, the association between hsa-miR-182-5p and esophageal neoplasms has been confirmed by previous method 54 . This method identified two new tumor suppressor miRNA, including miR-182-5p and miR-455-5p, of which has-miR-182-5p was confirmed to be associated with esophageal cancer.…”
Section: Comparison Of Our Methods With Different Classifiersmentioning
confidence: 52%